인공지능 기법을 이용한 MCT 가공 제품 품질에 영향을 미치는 특성에 대한 연구 - 유익수(Ik-Soo Yoo); 송준혁(Jun-Hyeok Song); 정희운(Hee-Woon Cheong) (한국정보통신학회논문지, 2024)
본 논문에서는 인공지능 기술 중 총 8종류의 머신러닝 지도학습 모델을 이용하여 MCT 가공 완제품의 불량 여부를 예측하는 연구를 하였다. 머신러닝 모델 간 성능지표 및 소요 실행시간을 비교한 결과, XGBM, GBM, LightGBM 및 Stacking Ensemble 모델이 가장 우수한 정확도, 정밀도, 재현율, F1-점수, AUC 값을 보였으며, 이 중 Stacking Ensemble 모델이 가장 짧은 0.53초의 학습 소요 실행시간을 나타내어 빠른 불량 예측에 적합한 모델로 판단된다. 또한 불량에 영향을 미치는 특성 변수들의 상대적 중요도를 XGBoost 모델로 분석한 결과, W-축 절대 좌표, X-축 절대 좌표가 다른 특성 변수들에 비하여 상대적으로 불량에 높은 영향을 미치는 것으로 나타났다. In this paper, a study was conducted to predict the defects in MCT processed finished products using a total of eight types of supervised learning models, one of the representative deep learning algorithms for artificial intelligence technologies. As a result of comparing the performance indicators and required execution time among machine learning models, it was confirmed that XGBM, GBM, LightGBM and Stacking Ensemble showed the highest accuracy, precision, recall, F1 score and AUC. Above all, it was confirmed that the Stacking Ensemble model was the most suitable algorithm for fast defect prediction because it showed the shortest learning execution time of 0.53 seconds. Besides, as a result of the analyzation of the relative importance of characteristic variables using the XGBoost model, it was found that the W-axis absolute coordinate and the X-axis absolute coordinate have a crucial effect on the defect. KCI Citation Count: 0